2022
DOI: 10.3390/microorganisms10101952
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of the SARS-CoV-2 Omicron BA.5/22B in Monaco

Abstract: The Omicron BA.5/22B variant has been designated as a “variant of concern” by the World Health Organization. We describe, here, the first evidence in Monaco of infection with an Omicron BA.5/22B variant, probably imported from the Republic of Seychelles, harboring a rare combination of non-BA.5/22B signature amino acid changes. SARS-CoV-2 neutralizing antibodies were measured with a surrogate virus neutralization test. SARS-CoV-2 genotype screening was performed on nasopharyngeal samples with a multiplex qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The sequence variation or the mutation rate establishes an omicron variant dissimilar to the α variant as analyzed by polyphyletic classification based on the Neighbor-Joining methodology (MEGA-X) [ 39 ]; this establishes a probability about the rate of single nucleotide polymorphism, which directly causes a change in sequence, structure, and function of omicron variants. After the determination of position in the phylogenetic tree, analysis of functional variability among proteomes of different variants by computational methods shows a change in the surface charge in omicron spike protein compared to other variants due to mutation, which directly results in the increment of hydrophobic residues; this increase enhances the stability of the omicron protein core [ 40 , 41 ], while the change in the amino acids of the omicron RBD region of spike protein in comparison to other lineages affects the immune response and also the vaccine (Ab) interaction [ 42 , 43 ]. The transition from Proline-603 to lysine-730, aspartic acid 655 to valine 782, aspartic acid 669 to glycine 796, and many more in Omicron in comparison to α increase the positive charge and hydrophobicity, which improves its binding with hACE2(due to negative charge of protein) and stability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sequence variation or the mutation rate establishes an omicron variant dissimilar to the α variant as analyzed by polyphyletic classification based on the Neighbor-Joining methodology (MEGA-X) [ 39 ]; this establishes a probability about the rate of single nucleotide polymorphism, which directly causes a change in sequence, structure, and function of omicron variants. After the determination of position in the phylogenetic tree, analysis of functional variability among proteomes of different variants by computational methods shows a change in the surface charge in omicron spike protein compared to other variants due to mutation, which directly results in the increment of hydrophobic residues; this increase enhances the stability of the omicron protein core [ 40 , 41 ], while the change in the amino acids of the omicron RBD region of spike protein in comparison to other lineages affects the immune response and also the vaccine (Ab) interaction [ 42 , 43 ]. The transition from Proline-603 to lysine-730, aspartic acid 655 to valine 782, aspartic acid 669 to glycine 796, and many more in Omicron in comparison to α increase the positive charge and hydrophobicity, which improves its binding with hACE2(due to negative charge of protein) and stability [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly recommended to protect people from CoViD-19. Two vaccines are offered by the NVC to people wishing to be vaccinated against SARS-CoV-2: the Comirnaty Original vaccine and the Comirnaty Original/Omicron BA.4-5 vaccine from the Pfizer/BioNTech laboratories [16,17]. The Comirnaty Original/Omicron BA.4-5 vaccine is offered to people with a complete vaccination schedule (two doses or a single dose following a SARS-CoV-2 infection), regardless of the previously administered vaccine.…”
Section: Vaccinationmentioning
confidence: 99%
“…The B.1 lineage, which is regarded as the ancestral lineage and is less developed than the VoC above, may have originated during the COVID-19 outbreak in northern Italy in early 2020, as demonstrated [3]. A novel SARS-CoV-2 variant (B.1.1.529) was discovered in South Africa from a patient sample on November 9, 2021, and the WHO named it the Omicron variant on November 26 [4]. Due to a signi cant number of mutations (particularly in the spike protein), studies have shown that Omicron variants exhibit increased transmissibility, high receptor binding a nity, and evasion of naturally occurring infection or vaccine-induced immunity [5].…”
Section: Introductionmentioning
confidence: 97%
“…The three SARS-CoV-2 variants that predominated during that time all belonged to different genotypes, as revealed by whole genome sequencing and genomics analysis. The BA.2 variant prevalent in 2022 and the BA.5 variant prevalent in 2023 were both members of the Omicron lineage [4], while the B.1 variant prevalent in 2021 belonged to the ancestral lineage [3]. In this study, the Ct values of the ORF1ab gene and the N gene of SARS-CoV-2 in oropharyngeal swabs of patients with COVID-19, the negative conversion time of nucleic acid, clinical performance of patients with COVID-19, and blood test levels were compared and analyzed in order to investigate the characteristics of molecular biological tests and other laboratory tests for different genotypes of SARS-CoV-2, as well as the differences in clinical performance, and to provide a reference for the diagnosis and treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation